Elevated ratio of urinary metabolites of thromboxane and prostacyclin is associated with adverse cardiovascular events in ADAPT. - Thomas J Montine; Joshua A Sonnen; Ginger Milne; Laura D Baker; John C S Breitner (PLoS ONE)
Results from prevention trials, including the Alzheimer's Disease Anti-inflammatory Prevention Trial (ADAPT), have fueled discussion about the cardiovascular (CV) risks associated with non-steroidal anti-inflammatory drugs (NSAIDs). We tested the hypotheses that (i) adverse CV events reported among ADAPT participants (aged 70 years and older) are associated with increased ratio of urine 11-dehydrothromboxane B(2) (Tx-M) to 2'3-donor-6-keto-PGF1 (PGI-M) attributable to NSAID treatments; (ii) coincident use of aspirin (ASA) would attenuate NSAID-induced changes in Tx-M/PGI-M ratio; and (iii) use of NSAIDs and/or ASA would not alter urine or plasma concentrations of F(2)-isoprostanes (IsoPs), in vivo biomarkers of free radical damage. We quantified urine Tx-M and PGI-M, and urine and plasma F(2)-IsoPs from 315 ADAPT participants using stable isotope dilution assays with gas chromatography/mass spectrometry, and analyzed these data by randomized drug assignment and self-report compliance as well as ASA use. Adverse CV events were significantly associated with higher urine Tx-M/PGI-M ratio, which seemed to derive mainly from lowered PGI-M. Participants taking ASA alone had reduced urine Tx-M/PGI-M compared to no ASA or NSAID; however, participants taking NSAIDs plus ASA did not have reduced urine Tx-M/PGI-M ratio compared to NSAIDs alone. Neither NSAID nor ASA use altered plasma or urine F(2)-IsoPs. These data suggest a possible mechanism for the increased risk of CV events reported in ADAPT participants assigned to NSAIDs, and suggest that the changes in the Tx-M/PGI-M ratio was not substantively mitigated by coincident use of ASA in individuals 70 years or older.